Role of Siberia in Eurasian Stories of Russian Political and Economic Thought - Donskikh, Oleg A. (Zenodo, 2021)
Russia was and remains to be a Eurasian territory in terms of its geographic location. However, there is nothing specifically Eurasian, either ideologically, politically, culturally or economically, that would make it possible to speak seriously about Eurasianism as a basis for future international political and economic integration of different countries around Russian Siberia and – more broadly – Russia as its centre, without considerable economic achievements of Russia and serious financial inflows in the Siberian economy. The colossal space of Russian Siberia with scattered spots of current economic exploitation activity primarily designed and operated for excavation of natural resources, cannot serve the purposes of Eurasian integration in any way. There remain serious opportunities associated with the development of the Arctic territories, but they can serve Eurasian integration purposes only if large infrastructure projects are implemented that would link the southern and northern zones of Siberia into a single economic space.